Caterpillar salivary enzymes: "eliciting" a response - Merkx-Jacques, Magali; Bede, Jacqueline (Phytoprotection, 2004)
AbstractPlants exhibit remarkable plasticity in their ability to differentiate between herbivorous insect species and subtly adjust their defense responses to target distinct pests. One key mechanism used by plants to recognize herbivorous caterpillars is elicitors present in their oral secretions; however, these elicitors not only cause the induction of plant defenses but recent evidence suggests that they may also suppress plant responses. The absence of “expected changes” in induced defense responses of insect-infested plants has been attributed to hydrogen peroxide produced by caterpillar salivary glucose oxidase (GOX). Activity of this enzyme is variable among caterpillar species; it was detected in two generalist caterpillars, the beet armyworm (Spodoptera exigua) and the bertha armyworm (Mamestra configurata), but not in other generalist or specialist caterpillar species tested. In the beet armyworm, GOX activity fluctuated over larval development with high activity associated with the salivary glands of fourth instars. Larval salivary GOX activity of the beet armyworm and the bertha armyworm was observed to be significantly higher in caterpillars reared on artificial diet as compared with those reared on Medicago truncatula plants. This implies that a factor in the diet is involved in the regulation of caterpillar salivary enzyme activity. Therefore, plant diet may be regulating caterpillar oral elicitors that are involved in the regulation of plant defense responses: our goal is to understand these two processes.